ChemInform Abstract: Mechanisms for Enhanced Performance of Platinum‐Based Electrocatalysts in Proton Exchange Membrane Fuel Cells. Issue 18 (17th April 2014) - Su, Liang; Jia, Wenzhao; Li, Chang‐Ming; Lei, Yu
Abstract: Review: 142 refs.